Solid-State Bioconversion of Pineapple Residues into Kojic Acid by Aspergillus flavus: A Prospective Study - Nurashikin, S.; Rusley, E. Z.; Husaini, A. (World Academy of Science, Engineering and Technology, 2013)
—Kojic acid is an organic acid that is widely used as an ingredient for dermatological products, precursor for flavor enhancer and also as anti-inflammatory drug. The present study was undertaken to test the feasibility of pineapple residues as substrate for kojic acid production by Aspergillus flavus Link 44-1 via solid-state fermentation. The effect of initial moisture content, pH and incubation time on kojic acid fermentation was investigated. The best initial moisture content for kojic acid production from pineapple residues was observed at 70% (v/w) whereas initial culture pH 2.5 was identified to give high production of kojic acid. The optimal range of incubation time was identified between 8 and 14 days of incubation which corresponded to highest range of kojic acid produced. The results from this study pronounce the promising usability of pineapple residues as alternative substrate for kojic acid production by A. flavus Link 44-1.